Controlling Crystallization, Mechanical Properties and Heat Resistance of Poly(L-lactide)-b-polyethylene glycol)-b-poly(L-lactide) Bioplastic by Melt Blending with Low Molecular Weight Poly(D-lactide)/Poly(L-lactide) Mixtures - Baimark, Yodthong; Phromsopha, Theeraphol (Asian Journal of Chemistry, 2022)
The crystallization behaviour, mechanical properties and heat resistance were determined for mixtures of poly(L-lactide)-b-polyethylene glycol-b-poly(L-lactide) (PLLA-PEG-PLLA) blended with poly(D-lactide)/poly(L-lactide) with m.w. of 6,000 g/mol (PDLA6k/PLLA6k). These blends were prepared by melt blending. PLLA-PEG-PLLA/PDLA6k/PLLA6k ratios of 90/10/0, 90/7.5/2.5, 90/5/5, 90/2.5/7.5 and 90/0/10 %wt. were investigated. PLLA-PEG-PLLA/PDLA6k and PLLA-PEG-PLLA/PLLA6k blends were also prepared for comparison. The presence of PDLA6k/PLLA6k mixture improved crystallization and heat resistance of PLLA-PEG-PLLA and this improvement was related to increased PDLA6k content. However, the 90/10/0 blend film was brittle but 90/7.5/2.5, 90/5/5, 90/2.5/7.5 and 90/0/10 blend films were not. The PLLA6k blending enhanced film flexibility. The results suggested that the PLLA-PEG-PLLA blends with controllable mechanical properties and heat resistance can be prepared by varying the PDLA6k/PLLA6k ratio for use as flexible and heat-resistant biodegradable bioplastics.